Static test compaction procedure for large pools of multicycle functional broadside tests. Issue 5 (3rd July 2018) - Pomeranz, Irith
Abstract : This study describes a static test compaction procedure that is applicable in the scenario where (i) a large pool of tests can be generated efficiently, but (ii) test compaction that modifies tests, and covering procedures, are not applicable, and (iii) reverse order fault simulation procedures are not sufficient for test compaction. The procedure has the ability to identify tests in the pool that are effective for test compaction even when they do not increase the fault coverage. This ability is achieved using only fault simulation with fault dropping. The procedure is designed for the case where multicycle functional broadside tests are extracted from functional test sequences. The use of multicycle tests results in higher levels of test compaction than possible with two‐cycle functional broadside tests. It adds another dimension to the procedure that also needs to select a number of clock cycles for every test.